Hierarchical porous NiCo2O4 nanosheet arrays directly grown on carbon cloth with superior lithium storage performance. Issue 14 (23rd March 2017) - Zhao, Li; Wang, Lei; Yu, Peng; Tian, Chungui; Feng, He; Diao, Zhongwei; Fu, Honggang
Abstract : The hierarchical structures of porous NiCo2 O4 nanosheets directly grown on a conductive carbon cloth substrate were obtained by a facile in situ synthetic strategy, which could exhibit satisfactory performance with high discharge capacity, superior rate capacity and excellent reversibility. Abstract : Binary metal oxides have been explored as advanced candidates in lithium-ion battery (LIB) anodes due to their high specific capacity. Herein, the hierarchical structures of porous NiCo2 O4 nanosheets directly grown on a conductive carbon cloth substrate (3D NCO-PSA/CC) were obtained by a facile in situ synthetic strategy. When applied as a binder-free LIB anode, it exhibited satisfactory performance with a high discharge capacity (a first discharge capacity of 2090.8 mA h g −1 and a stable capacity of 1687.6 mA h g −1 at 500 mA g −1 ), superior rate capacity (discharge capacity of 375.5 mA h g −1 at 6000 mA g −1 ) and excellent reversibility (coulombic efficiency of approximately 100%). The outstanding performances should be attributed to the 3D porous structures, nanosheets and good conductivity of NCO-PSA/CC that could not only ensure the rapid transport of Li + ions and electrons but also remit the huge volume change during lithiation/delithiation processes. Undoubtedly, the present facile and effective strategy can be extended to other binary metal–oxide materials for use as high-performance energy storage and conversion devices.